Mixing Characteristics and Bubble Behavior in an Airlift Internal Loop Reactor with Low Aspect Ratio - 张伟鹏 雍玉梅 张广积 杨超 毛在砂 (Chinese journal of chemical engineering, 2014)
The present study summarizes the results of macro-and micro-mixing characteristics in an airlift inter-nal loop reactor with low aspect ratio （H/D≤5） using the electrolytic tracer response technique and the method of parallel competing reactions respectively. The micro-mixing has never been investigated in airlift loop reactors. The dual-tip electrical conductivity probe technique is used for measurement of local bubble behavior in the reactor. The effects of several operating parameters and geometric variables are investigated. It is found that the increase in su-perficial gas velocity corresponds to the increase in energy input, liquid circulation velocity and shear rate, decreas-ing the macro-mixing time and segregation index. Moreover, it is shown that top clearance and draft diameter affect flow resistance. However, the bubble redistribution with a screen mesh on the perforated plate distributor for macro-mixing is insignificant. The top region with a high energy dissipation rate is a suitable location for feeding reactants. The analysis of present experimental data provides a valuable insight into the interaction between gas and liquid phases for mixing and improves the understanding of intrinsic roles of hydrodynamics upon the reactor de-sign and operating parameter selection.